A Survey of Chick Mortality at Hatching in three Selected Hatcheries in Jos, Central Nigeria - Muhammad, M.; Muhammad, L.U.; Mani, A.U.; Ambali, A.G. (International Journal of Poultry Science, 2009)
A questionnaire-based survey was conducted to investigate chick mortality at hatching in three commercial hatcheries in and around Jos, central Nigeria. Mortality was defined as the sum of dead chicks, dead-in-shell embryos and culls due to various other reasons. There was a large variation in culling rates due to poor hatching. The major reasons for culling were dead-in-shell embryos, weak chicks, dead chicks, omphalitis and physical abnormalities such as incomplete feathering, weak limbs, distorted beaks and wetness. There was no significant correlation between the age of breeding flock and percentage of culls indicating that culling rate was not strongly influenced by the age of breeding flock. Although, factors contributing to poor hatching include management and incubation failures, the most probable cause of abnormalities, weak chicks and omphalitis are diseased breeder flocks or poor hygiene and sanitation in hatchery operations. Two of the hatcheries used a combination of formaldehyde and iodine for disinfection but hygiene standards were compromised due to inadequate cleaning in all three hatcheries. The poor hatch experienced in this study suggests that there is considerable room for improvement in hatchery operations particularly with regards to hygiene and sanitation. Adequate training of hatchery operators in understanding the crucial role hygiene plays in ensuring high chick quality is needed.